1996
DOI: 10.1002/eji.1830260115
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities in the A2.1‐restricted cytotoxic T cell repertoire in humans and human leukocyte antigen‐transgenic mice

Abstract: HLA-A2.1-binding peptides (n = 38) were screened for immunogenicity with human peripheral blood mononuclear cells in cytotoxic T lymphocyte (CTL) induction experiments in vitro and with splenocytes from HLA-A2.1/Kb transgenic mice following immunization in vivo. These data were compiled and analyzed to determine the level of overlap between the A2.1-restricted CTL repertoire of A2.1/Kb-transgenic mice and A2.1+ humans. In both humans and mice, a major histocompatibility complex affinity threshold of approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 24 publications
5
77
0
Order By: Relevance
“…Peptides were given a net score integrating these data [iTopia iScore; supporting information (SI) Transgenic Mice. We used HLA class I transgenic mice to screen for high-affinity cdr2-specific CTLs, because such mice have been used to study immune responses to human tumor antigens (13,15). Immunizing AAD HLA-A2.1 transgenic mice with recombinant adenovirus-expressing full-length human cdr2 (Ad-hcdr2) yielded robust ex vivo CD8 ϩ T cell responses (frequency Ͼ0.3%) specific for cdr2 (290); weaker responses were seen to six other peptides, and these were not pursued further.…”
Section: Identification Of Cdr2mentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides were given a net score integrating these data [iTopia iScore; supporting information (SI) Transgenic Mice. We used HLA class I transgenic mice to screen for high-affinity cdr2-specific CTLs, because such mice have been used to study immune responses to human tumor antigens (13,15). Immunizing AAD HLA-A2.1 transgenic mice with recombinant adenovirus-expressing full-length human cdr2 (Ad-hcdr2) yielded robust ex vivo CD8 ϩ T cell responses (frequency Ͼ0.3%) specific for cdr2 (290); weaker responses were seen to six other peptides, and these were not pursued further.…”
Section: Identification Of Cdr2mentioning
confidence: 99%
“…We screened a complete cdr2 peptide library for HLA-A2.1 binding and evaluated immunogenicity and natural processing using HLA-A2.1 transgenic mice previously used to evaluate human tumor-associated antigens (13)(14)(15). Immunization of these mice with adenovirus expressing human cdr2 allowed us to isolate a high-avidity CD8-independent cdr2-specific CTL clone and the genes encoding its T cell receptor (TCR) ␣-and ␤-chains.…”
mentioning
confidence: 99%
“…12 We have recently employed HLA-A2 (AAD) transgenic mice to characterize immune responses to E7 DNA vaccines. 13 As HLA-A2 transgenic mice also express murine MHC class I molecules (H-2D b and K b ), when HLA-A2 transgenic mice were vaccinated with DNA encoding CRT linked to wild-type E7, the vaccinated mice generated predominantly H-2D b -restricted E7-specific CD8…”
Section: Combination Of Hpv E6 and E7 Dna Vaccines S Peng Et Almentioning
confidence: 99%
“…We observed that the presence of the E7 49-57 aa sequence within the E7 gene of the CRT/E7 DNA vaccine suppresses the efficient activation of HLA-A2 restricted E7 (aa [11][12][13][14][15][16][17][18][19][20] peptide-specific CD8 + T cell-mediated immune responses 13 in HLA-A2 transgenic mice. In order to avoid this situation and accurately characterize the HLA-A2-restricted E7-specific CD8 + T-cell immune response in HLA-A2 transgenic mice, we generated pcDNA3-CRT/ mtE7(del aa49-57), a DNA vaccine that deletes aa49-57 from the E7 gene.…”
Section: Combination Of Hpv E6 and E7 Dna Vaccines S Peng Et Almentioning
confidence: 99%
“…Thus, the HLA-A2 transgenic mice may potentially be useful for evaluating HLA-A2-restricted CD8 responses with specificities correlating with those observed in humans. 4 We have acquired HLA-A2.1(AAD) transgenic mice that express a chimeric HLA class I molecule, comprising the a-1 and a-2 domains from human HLA-A*0201 and the a-3 transmembrane/cytoplasmic domain from mouse H-2D d . 5 These transgenic mice have been used by other researchers to characterize the immunogenicity and vaccine effects of several HLA-A2-restricted CTL epitopes from viral antigens.…”
Section: Introductionmentioning
confidence: 99%